"Sacralization" of the body in contemporary culture. A philosophical perspective = "Sakralizacja" ciała w kulturze współczesnej. Perspektywa filozoficzna - Guzowska, Beata (Przegla̜d religioznawczy, 2021)
In contemporary culture, many categories are separated from metaphysical premises. Currently, man feels called to create his unique lifestyle, to pursue his humanity free from external religious, social, or political influences. Today’s somatic turn in culture means that the body is seen as the source of all values. This turn is directed not so much at the outer form of the body but our inner experience and spirituality. Secularization encourages us to consider ourselves, our happiness, in more earthly and carnal terms with almost religious adoration.